Investment and Dividend Policy of Oil and Gas and other Russian Companies: Financial Aspect - Gaponenko, V.F.; Zhukova, O.I.; Alaberdeev, R.R.; Kilyskhanov, Kh.Sh.; Teterina, E.A. (Journal of Reviews on Global Economics, 2018)
In the article features of formation of investment and dividend policy of oil and gas and other the Russian companies are presented: financial aspect, existing problems are revealed and the corresponding recommendations are offered. The extensive world practice and its invaluable experience in the field of formation of effective investment and dividend policy can help to solve a number of problems to the Russian public joint-stock companies. The analysis, systematization and generalization of the theory and practice of payment of dividends by Russian joint-stock companies are carried out, forecasts are made. Â